Kajian Kesulitan Belajar Membaca Menulis Permulaan (MMP) di Sekolah Dasar: Study of Difficulty Learning to Read Beginning Writing (MMP) in Primary School - Widyaningrum, Heny Kusuma; Hasanudin, Cahyo (Universitas Muhammadiyah Sidoarjo, 2019)
The aims of this research are: 1) to investigate the type of learning difficulties in initial reading and writing faced by second grade students, 2)the factors that caused them having learning difficulties in initial reading and writing. The approach is descriptive qualitative research in form of case study. The subjects of research are second grade students of elementary school 01 Sumoroto, Ponorogo. The data collection techniques are obtained using documentations and interviews. The data obtained are non-statistic data. The data are analysed using interactive models, namely data reduction, data presentation, data conclusion and verification. The results of the study are (1) the type of learning difficulties, in initial reading and writing faced by second grade students of elementary school 01 Sumoroto, namely students that are not fluent in spelling, less clear pronunciation, lack of letters memorization, difficult to distinguish letters, incomplete of words writing, difficulties in composing sentences; (2) the factors that caused learning difficulties in reading and writing are adolescence, love to play rather than learning,like to be a trouble maker in class, study at home when the teacher gives homework, lack of attention, less motivation, and the teacher is less assertive.